Q-Float in West Ulster English and labeling - Blümel, Andreas (Yearbook of the Poznan Linguistic Meeting, 2018)
In this paper I contrast a stranding analysis of Q-float in intermediate A′-positions in West Ulster English with the labeling analysis of successive-cyclic A′-movement and show that the former represents a problem for the latter. If we want to retain the labeling analysis, alternatives to stranding must come forward, some of which I discuss here.